Rootabaga stories - Sandburg, Carl, 1878-1967.; Petersham, Maud, 1890-1971; Petersham, Miska, 1888-1960 (San Diego : Harcourt Brace Jovanovich, 1990)
Presents Sandburg's fanciful, humorous tales peopled with such characters as the Potato Face Blind Man, the Blue Wind Boy, and many others.
"An Odyssey classic."
Keywords: Fairy tales -- United States; Children's stories, American; Fairy tales; Short stories